Observation of staging during intercalation in layered alpha-cobalt hydroxides: a synthetic and kinetic study. - Du, Y; O'Hare, D (2008)
The anion-exchange reaction of the layered alpha-cobalt hydroxides Co(OH)(1.75)(DDS)(0.25).0.6H(2)O (1) and Co(OH)(1.7)Cl(0.3).0.4H(2)O (3) with carbonate has been investigated. For 3 the reaction proceeds by complete displacement of the interlayer Cl(-) anions by CO(3)(2-) to give Co(OH)(1.7)(CO(3))(0.15).0.6H(2)O (4). Remarkably for 1 we only observe ion-exchange of the DDS(-) from every other layer to give the second stage intercalate Co(OH)(1.75)(DDS)(0.07)(CO(3))(0.09).0.5H(2)O (2). The kinetics of these processes have been investigated using time-resolved in situ energy dispersive XRD and small/wide-angle X-ray scattering. In both cases the reaction order (n) was found to be consistent with a two-dimensional diffusion controlled model. Both 3 and 4 are magnetically ordered, and dc and ac magnetic susceptibility measurements have been used to explore their 3D ferrimagnetically ordered ground states.